Evaluation of lipid nanoparticles for topical delivery of protocatechuic acid and ethyl protocatechuate as a new photoprotection strategy - Daré, Regina G.; Costa, Ana; Nakamura, Celso V.; Truiti, Maria C.T.; Ximenes, Valdecir F. [UNESP]; Lautenschlager, Sueli O.S.; Sarmento, Bruno (Elsevier, 2020)
Excessive exposure to solar radiation induces injurious effects on human skin. Our previous study evidenced that protocatechuic acid (P0) and ethyl protocatechuate (P2) act against photodamage and photoaging. The present study aimed to develop solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) for topical delivery of P0 or P2, as a strategy for photoprotection. Lipid nanoparticles exhibited mean particle size, polydispersity index, zeta potential and association efficiency between 200 and 400 nm, 0.160 to 0.460, −2.2 to −5.2 mV, and 60% to 80%, respectively. The formulations were stable for 3 months when stored at 4○C and 25○C/60% RH. SLNs/NLCs-P0 showed minor cytotoxicity effects compared with SLNs/NLCs-P2, in HaCat (keratinocytes) and HFF-1 (fibroblasts) cell lines. Additionally, bare NLCs exhibited less cytotoxicity effect, compared with bare SLNs. NLCs exhibited a controlled in vitro release of P0 and P2, and were able to protect the compounds against UVB degradation. Ex vivo permeability study showed that NLCs modulated P0 and P2 retention profiles on human skin layers. Furthermore, histological analysis of skin showed that NLCs-P0 did not cause morphological alterations, while NLCs-P2 showed a potential irritation effect in the skin structure. Based on these results, NLCs were considered a potential dermatological nanocarrier for P0 delivery.
Keywords: Ethyl protocatechuate; Franz cells; Nanostructured lipid carriers; Protocatechuic acid; Solid lipid nanoparticles; Topical delivery